On the transition probabilities confidence interval evaluation in the syndromic analysis - Bikelis, Algimantas; Dapkūnas, Sigitas; Meilūnas, Mečislovas; Stoškuvienė, Danutė (Lietuvos matematikos rinkinys, 2001)
A confidence interval evaluation problem of transition probabilities is considered.